Pengukuran Efisiensi Proses PPDB dengan Pendekatan Work Measurement - Vitri Nur Hidayati; Muhamad Abdul Jumali (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to measure the process efficiency of student admission (PPDB) using a work measurement approach by comparing manual and digital systems at a private vocational school in Surabaya. A quantitative–comparative design was applied to ten complete admission process records, evaluating three indicators: process time, administrative error rate, and staff workload. Data were collected through structured time study, error logging, and daily task records during one admission period. The results indicate that the digital system reduces process time by 50–90%, decreases the error rate from 15% to 5%, and improves staff productivity by minimizing overtime. The three indicators were integrated into a composite efficiency index adapted from Overall Equipment Effectiveness (OEE), yielding 18.7% for the manual system and 80.7% for the digital system. These findings confirm that digitalization significantly enhances service process performance and provides a measurable industrial engineering framework for improving administrative efficiency.